The Effect of Trade Facilitation on Trade Margin of 8 ASEAN-China Free Trade Area Countries (ACFTA): A Gravity Model Approach - susetyo, ferdyan; Handoyo, Rossanto Dwi (Journal of Developing Economies, 2016)
Trade facilitation is an effort of simplification and harmonization of international trade procedures. Trade facilitation that manifested in the form of policy packages that aim to reduce trade costs and improve export growth. Export growth can be sourced from the level of diversity of exported goods (extensive margin) and the volume of exported goods (intensive margin). This study aims to analyze the effect of trade facilitation on the extensive and intensive margin of trade eight member countries of ACFTA during the years 2006-2014. Trade facilitation indicators used in this study consisted of exporters and importers port efficiency. This study uses gravity model and estimation techniques Random Effect Model. The results showed that exporter port efficiency have a positive and significant effect on the extensive margin while importer port efficiency has a positive and significant effect on the intensive margin. Keywords: Trade Facilitation, Extensive Margin, Intensive Margin, ACFTA (ASEAN-China Free Trade Area), Gravity Model.JEL: F13